Investigating the Relationship between staff health literacy and quality of life in Famennian County: A Cross-Sectional Study - Majid Barati; Sahar Bijari; Mahshad Taherpour; Maryam Afshari (Mashhad University of Medical Sciences, 2019)
Background and objectives: Given the importance of the role of health literacy in promoting quality of life, as well as the role that physicians and health professionals play in promoting health behaviors and public awareness in terms of people's acceptance of information and trust, the study needs special attention; The aim of this study was to determine the relationship between health literacy and quality of life in health care workers in Famenin County. Materials and Methods: This descriptive-analytic study was conducted on 275 Health care worker in Famenin County in 2018 using census method. The adults' health literacy questionnaire (HELIA) and quality of life questionnaire (SF-36) were used to collect data. Data were analyzed using SPSS24 software. Results: The results showed that 32.4 percent had not enough health literacy. Also, 64.1% of participants achieved the maximum quality-of-life score that indicated a relatively favorable situation. Quality of life was correlated with health literacy (r =0.252, P<0.01). By increasing the score of the assessment and application of health information, the average quality of life score increased by 0.82 and 1.10, respectively. Conclusion: In general, the findings of this study showed a significant relationship between the level of health literacy and quality of life, which indicates the key role of health literacy in improving quality of life. Therefore, health literacy should be considered as a factor in promoting health behaviors and creating healthy lifestyles and ultimately improving the quality of life.